6 - Le coupé décalé en Côte d’Ivoire : Sens et enjeux d’un succès musical - Franck Gawa (African Sociological Review, 2015)
This article is an explanatory contribution of the current success of the cut offset a new Ivorian musical genre occurred in the corridors of the Ivorian crisis. His current success is not unrelated to the phenomenon of globalization, but the factor that seems decisive is once again its specific link with the political imagination of urban youth. Of young people through this musical style expand social boundaries of power in Cote d’Ivoire. These call into crisis symbolic efficacy of political discourse by turning it as a motivating factor for repositioning on the social ladder of power.